Correlation between Psychosomatic Assessment, Heart Rate Variability, and Refractory GERD: A Prospective Study in Patients with Acid Reflux Esophagitis - Hsin-Ming Wang; Pao-Yuan Huang; Shih-Cheng Yang; Ming-Kung Wu; Wei-Chen Tai; Chih-Hung Chen; Chih-Chien Yao; Lung-Sheng Lu; Seng-Kee Chuah; Yu-Chi Lee; Chih-Ming Liang (Life, 2023)
Background: Gastroesophageal reflux disease (GERD) affects a significant proportion of individuals, with life stress being a contributing factor. This study aimed to investigate the correlation between psychosomatic evaluations, heart rate variability (HRV), and GERD in a cohort of individuals. Additionally, the study aimed to analyze the sequencing changes following proton pump inhibitor (PPI) treatment and identify predictive factors associated with refractory GERD. Methods: A prospective cohort of 105 individuals with reflux esophagitis and a control group of 50 participants without acid reflux symptoms were enrolled. Psychosomatic evaluations, including GERDQ, GERDQLQ, RSI, BAI, BDI, and SSS-8, were assessed at baseline and during treatment. HRV parameters were also evaluated. Multivariate analysis was used to identify predictive factors for refractory GERD. PPIs were administered regularly for the initial 2 months and then used on-demand. Refractory GERD was defined as less than 50% improvement in symptom relief or GERDQLQ score ≥ 20 after 8 weeks of PPI treatment. Results: The GERD group had higher scores in all psychosomatic evaluations compared to the control group (all p-values < 0.001). There were no significant changes in any parameters of HRV before and after treatment in the GERD group. Strong and consistent correlations were observed between GERD symptoms and psychological scores (BAI, BDI, and SSS-8) across all time points (W0, W4, and W8). Sequential reductions in GERD symptom scores and psychosomatic evaluations were observed during the initial eight weeks of treatment. Higher GERDQ (≥10) and SSS-8 (≥12) scores were predictive of refractory GERD (p = 0.004 and p = 0.009, respectively). Conclusions: This study emphasizes the importance of considering physiological and psychological factors in the management of GERD. Psychosomatic evaluations provide valuable insights for assessing and treating GERD patients. Integrating stress management and comprehensive assessments into personalized treatment strategies is crucial.